Gender effects of education on economic development in Turkey - Aysit Tansel; Nil Demet Güngör (Institute for the Study of Labor (IZA), 2012)
Several recent empirical studies have examined the gender effects of education on economic growth or on steady-state level of output using the much exploited, familiar cross-country data in order to determine their quantitative importance and the direction of correlation. This paper undertakes a similar study of the gender effects of education using province level data for Turkey. The main findings indicate that female education positively and significantly affects the steady-state level of labor productivity, while the effect of male education is in general either positive or insignificant. Separate examination of the effect of educational gender gap was negative on output. The results are found to be robust to a number of sensitivity analyses, such as elimination of outlier observations, controls for simultaneity and measurement errors, controls for omitted variables by including regional dummy variables, steady-state versus growth equations and considering different samples.
urn:nbn:de:101:1-2012081612237
Keywords: O11; O15; I21; J16; 330; labor productivity; economic development; education; gender; Turkey; Frauenbildung; Makroökonomischer Einfluss; Arbeitsproduktivität; Wirtschaftswachstum; Türkei